Pengaruh Model Brain Based Learning Terhadap Pemahaman Konsep dan Kemampuan Berpikir Kritis Fisika SMA - Ni Putu Devi Maretha Widyantari; Syahrial Ayub; Jannatin 'Ardhuha (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2020)
This research aims to determine (1) the influence of brain based learning (BBL) models on the understanding of physics concepts among high school students, (2) the influence of BBL models on physics critical thinking ability among high school students, and (3) the influence of BBL models on conceptual understanding and the critical thinking ability among high school students. This research is a quasi-experiment and uses non-equivalent control group design with pre-test and post-test design. The population were all students of class X MIPA of SMAN 1 Gerung in the academic year of 2018/2019. Samples were taken using purposive sampling technique. The experimental class is treated using the BBL model while the control class uses the expository learning model. The hypothesis used are the polled variance t-test and Manova test. Based on the results of the analysis, it can be concluded that (1) there are influences of BBL models on the understanding of physics concepts among high school students (2) there are influences of the BBL modesl on physics critical thinking ability among high school educators, and (3) there are influences of BBL ÃÂ models on conceptual understanding and critical thinking ability in physics among high school student.